Voices from within: Students’ lived experiences on English language anxiety - Roselle Matammu Soriano; Annalene Grace Co (Institute of Advanced Engineering and Science, 2022)
Recent developments in language studies showed a great need for effective communication in a globalized world. The participants' language anxiety data was collected using a qualitative research design with phenomenology as the topic of inquiry. To acquire information, focus group discussion was utilized to investigate the factors influencing the anxiety of students in learning the English language. Additionally, the study involved 24 students from Quirino State University in the Philippines' Colleges of Education, Arts & Sciences, Criminology, Engineering, Hospitality Management, Business Administration, Computing Sciences, and Midwifery. The participants were selected using purposive sampling. Findings of the study showed that teacher factor, inability to express ideas, lack of confidence, fear of committing mistakes and negative comments, family factor, fear of English classes, and lack of vocabulary/ideas were the factors that greatly influenced the anxiety of students in learning the English language. Owing to the results of the study, it is recommended that instructors/professors should be aware of the presence of these anxiety-inducing factors in the classrooms and create an environment in which students can feel more at ease in English classes by employing a variety of strategies that allow learners to express themselves and maintain motivation in English language learning.